2022
DOI: 10.1371/journal.pone.0277542
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet indices as diagnostic and predictive biomarkers for comorbidity of diabetes and metabolic syndrome in southern Ethiopia: A comparative cross-sectional study

Abstract: Background Metabolic syndromes (MetS) and diabetes mellitus (DM) comorbidity is a growing major global public health problem with huge morbidity and mortality. It is a pro-inflammatory and prothrombotic disorder characterized by alteration of platelet indices and increased platelet activation, however, the tendency to use them in diagnosis is not yet fully evaluated in our context and there is limited evidence on the role of platelet indices in predicting and differentiating DM+MetS comorbidity in Ethiopia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Similarly, the correlation of inflammation and Mean Platelet volume has also been elaborated in the study conducted by wolkite university [12]. They concluded that there is a significant difference in the MPV between Diabetics and Healthy Controls.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, the correlation of inflammation and Mean Platelet volume has also been elaborated in the study conducted by wolkite university [12]. They concluded that there is a significant difference in the MPV between Diabetics and Healthy Controls.…”
Section: Discussionmentioning
confidence: 91%
“…A high MPV is associated with increased platelet production while a low MPV indicates decreased platelet production [ 22 ]. The biomarker role of MPV has been emphasized in different medical conditions including diabetes [ 23 ], metabolic syndrome [ 24 ], cancer [ 25 ], inflammatory bowel disease [ 26 ], preeclampsia [ 27 ], and ITP [ 16 ]. In ITP, an increased number of new platelets are formed in the bone marrow in response to excessive platelet destruction in the spleen.…”
Section: Introductionmentioning
confidence: 99%